Let's solve your system by substitution.
−3x+5y=−9;4x+8y=12
Step: Solve−3x+5y=−9for x:
−3x+5y=−9
−3x+5y+−5y=−9+−5y(Add -5y to both sides)
−3x=−5y−9
−3x
−3 = −5y−9 −3
(Divide both sides by -3)
x=
5
3
y+3
Step: Substitute
5
3
y+3forxin4x+8y=12:
4x+8y=12
4(
5
3
y+3)+8y=12
44
3
y+12=12(Simplify both sides of the equation)
44
3
y+12+−12=12+−12(Add -12 to both sides)
44
3
y=0
44
3
y
44
3
=
0
44
3
(Divide both sides by 44/3)
y=0
Step:
3 y+3:
x= 5
3 y+3
x= 5
3 (0)+3
x=3(Simplify both sides of the equation)
Answer:
x=3 and y=0